2020
DOI: 10.1101/2020.04.17.20069062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale implementation of pooled RNA-extraction and RT-PCR for SARS-CoV-2 detection

Abstract: Testing for active SARS-CoV-2 infection is a fundamental tool in public health measures taken to control the COVID-19 pandemic. Due to the overwhelming use of SARS-CoV-2 RT-PCR tests worldwide, availability of test kits has become a major bottleneck. Here we demonstrate the reliability and efficiency of two simple pooling strategies that can increase testing capacity about 5-fold to 7.5-fold, in populations with a low infection rate. We have implemented the method in a routine clinical diagnosis setting, and a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 31 publications
5
54
0
Order By: Relevance
“…However, appraising the performance of a pooling method exclusively by its efficiency would ignore one of the major drawbacks of pooling: loss of sensitivity due to dilution of the target. This issue becomes most pertinent when the viral load is low [9][10][11]13,14 . Our results confirm that all tested pooling methods suffer from false negatives, to a variable degree (Figure 2).…”
Section: Sensitivity Loss In Function Of Viral Loadmentioning
confidence: 99%
“…However, appraising the performance of a pooling method exclusively by its efficiency would ignore one of the major drawbacks of pooling: loss of sensitivity due to dilution of the target. This issue becomes most pertinent when the viral load is low [9][10][11]13,14 . Our results confirm that all tested pooling methods suffer from false negatives, to a variable degree (Figure 2).…”
Section: Sensitivity Loss In Function Of Viral Loadmentioning
confidence: 99%
“…Recently, several pooling tests for COVID-19 using probe-based assays have shown efficient viral detection. These studies have shown a wide range of pooling settings, from eight to 32 samples per pool, increasing up to 8 folds the testing efficiency compared to individual testing (Shenta et al, 2020;Viehweger et al, 2020;Ben-Ami et al, 2020). Here, we showed an efficient performance in the range of setting pools tested before the RNA extraction step, with an analytical sensitivity that shown that pooling setting between 5 to 20 samples per pool retain the accuracy of the test obtaining a shift to the right of the amplification curve up to 5.9 cycles in the dye-based assay and 4.4 cycles in the probe-based assay.…”
Section: Pooling Testmentioning
confidence: 99%
“…In spite of these idealizations, the practical utility of the predictions are quantitatively validated by recent SARS-CoV-2 pooled testing data. [2][3][4][5][6] The results indicate that pooled testing can significantly reduce the number of the SARS-CoV-2 tests required to identify each positive individual, even in populations with infection rates above 10%, although pooled testing is most advantageous in populations with lower infection rates. The field testing validation studies also confirm that the present predictions provide conservative testing efficiency estimates, as non-uniform clustering of infections is predicted to lead to an increase in testing efficiency, above that predicted assuming a uniform infection rate.…”
Section: Introductionmentioning
confidence: 98%
“…The optimal pool size, n, for a population with a given infection probability p was first obtained obtained by Dorfman 1 (and has since spawned numerous generalizations). 5,7,8 Here Dorfman's results are extended to yield practically useful predictions of the range of infection rates over which a given fixed pool size remains nearly optimal, as well as the significant additional efficiency that may be obtainable from using a second round of pooling for popula-3 tions with 0.001 ≤ p < 0.1 (0.1% ≤ p% < 10%). For a populations with a very low infection rate of 0.1%, the predicted 1st round optimal pool size is 32.…”
Section: Introductionmentioning
confidence: 99%